Accidents involving lithium-ion batteries in non-application stages: incident characteristics, environmental impacts, and response strategies - Ziyu Wang; Guohe Huang; Zhikun Chen; Chunjiang An (BMC Chemistry)
Abstract With the rapid growth of electric vehicle adoption, the demand for lithium-ion batteries has surged, highlighting the importance of understanding the associated risks, particularly in non-application stages such as transportation, storage, assembly, and disposal. This review explores the types and causes of lithium-ion battery accidents, categorizing them into leakage, fire, and explosion, often resulting from electrical, thermal, and mechanical abuses. It examines the environmental impacts of such incidents, including the release of toxic substances that threaten public health and ecological systems. The research also outlines the need for effective risk assessment methods and compliance with safety standards. Furthermore, it evaluates current emergency response strategies, advocating for a unified approach to managing these incidents. By delving into the complexities of lithium-ion battery safety, this study aims to contribute to improved practices and regulatory frameworks, ultimately enhancing related accident responses.